“My pockets are full”: The Emotional and Mechanical Function of Goodbyes in Animal Crossing - Kalinowski, Anna Maria (Loading, 2020)
This article focuses on goodbyes within the Animal Crossing series, describing them as an important but often overlooked mechanic afforded through the inventory space.  Beginning with defining the general mechanics withing the series, the article highlights the value of inventory space and argues that inventory space affords the central mechanic of collecting to emerge.  As inventory space is not infinite, collecting is accompanied by the necessary mechanic of goodbyes.  In order to make more room to collect players will be faced with choices of departing from both items and villagers, the game’s NPCs (Non-Playable Characters), emphasizing goodbyes’ mechanical and emotional function within this virtual world.  Ultimately, this article concludes by highlighting how these mechanics serve to emphasize the parasocial attachments and agency players encounter when faced with the dilemma of departure.